Performance characteristics of air distributor designs in a fluidized bed - Ahmmad Shukrie, Md Yudin (2017)
High pressure drop across the distributor for fluidizing air supply to the bed is one of major draw backs of the current air distributor designs. Besides, the mechanically assisted agitator and rotating distributor were installed to improve mixing inside the bed. Therefore, in order to minimize the cost of using high capacity blower as well as to reduce the energy, viable design of air distributors that can contribute to low pressure drop and improved particulate mixing in fluidized bed are essential. The present study aims to numerically and experimentally investigate the flow patterns and hydrodynamics in a fluidized bed operated with different configuration of distributors. The optimum mode of operation and the parameters that contribute to low pressure drop and improved particulate mixing in a fluidized bed is identified. The commonly used distributor designs are modified to suit in the fluidization operation with a low pressure blower. A fluidized bed column of 108 mm in diameter with six different air distributors; conventional perforated plate, multi-nozzles, and newly proposed slotted distributors with inclination angles of 90°, 67°, 45° and 30° are used in the simulations and experiment. In this study, 177 jim and 520 jim alumina and, 543 jim and 756 Pm river sands categorized in Geldart Group B particle are used to investigate the hydrodynamics of gas-solid fluidization. The numerical simulations by using the Re-Normalisation Group (RNG) k-s turbulent model show that when the inflow direction of the fluidizing air is inclined at 67°, 45° and 30° through the distributor slots, air flow pattern inside the bed is shown to produce swirling motion in a vicinity of the distributors. Also, the induced swirling air motion eliminates major dead zone regions. Experiment with bed materials show that at aspect ratio H/D0.4 and 0.5, the bed pressure drop is observed to be the lowest in the fluidized beds operated by 90° distributor and highest by the perforated plate distributor. Considerable increment of bed pressure drop is observed by 67°, 45° and 30° distributors as compared to 900. Interestingly, the minimum fluidization velocity is observed to take place promptly in a fluidized bed operated by 301 and 670 distributors. In other words, the fluidization occurred at low air flow rate in a bed operated by these inclined distributors. A continuous swirling bottom layer and a vigorously bubbling top layer are visible in a fluidized bed operated by 67°, 45° and 30° distributors. The degree of mixing is found to be influenced by the size and shape of bed materials in which intense mixing is observed by the fine bed and more stable mixing is spotted by the coarser bed. For all distributors, the distributor to bed pressure drop ratio is found to fall within the range of uniform operation of fluidization; except for the operation by using perforated plate distributor. The performance of the distributors is further assessed in terms of temperature distribution in the bubbling fluidization regime by using 67° and perforated distributors. Finally, a new pressure drop correlation is developed based on the Forchheimer-Ergun equation that takes into account the design parameter of the distributors with different inclination angles and different types of bed materials. The constants obtained through the regression analysis provided excellent predictions to the experimental data with maximum average error of 9%. In conclusion, a novel inclined 67° distributor is proposed as a new distributor for FBC due to lower pressure drop operation and improved particulate mixing as compared to conventional type distributors. This research finding could contribute to higher application of the fluidized bed technology, particularly in Malaysia where fluidized bed technology is still not popularly used in power generation plant using biomass as solid fuel.